Does digitalization make urban development greener? A case from 276 cities in China - Ma, Lindong; Xu, Weixiang; He, Shouchao; Hong, Yuanxiao; Yang, Weixia; Zhao, Yanping (Frontiers in Ecology and Evolution, 2023)
Nowadays countries in the world are striving to transform their economic and social development modes to achieve the general goal of green development. With the rapid development of communication technology and informatization, digitalization has already affected production and life, touching all aspects of society. Whether digitalization can make the world “greener”? To this end, this study conducts an empirical research based on the panel data of 276 cities in China from 2011 to 2020. Firstly, this paper separately measured the overall development level of urban digitalization and urban greening through the Entropy-TOPSIS method, then analyzed their spatial distribution characteristics and evolution process respectively, finally used the spatial Durbin model to explore the impact of digitalization on urban greening development. The following conclusions were drawn accordingly: 1. The spatial heterogeneity of urban digitalization is obvious, whose development pattern has changed from "multi-point" sporadic distribution to "group-type" aggregation. The gap among cities has not been improved. The Yangtze River Delta urban agglomeration has become an important high-level digital agglomeration area; 2. The spatial heterogeneity of urban greening development is also obvious. The difference between eastern regions and western regions is prominent, and the urban spatial agglomeration characteristics are distinct. However, the spillover effect is weakened with distance, and the convergence characteristics become obvious; 3. Digitalization is significantly beneficial to the development of urban greening with obvious spatial heterogeneity. Digitalization in urban agglomeration cities and eastern cities has a strong effect on the promotion of urban greening, while it is not obvious in western cities and non-urban agglomeration cities. Finally, according to the research results, suggestions for urban digitalization and greening development are put forward.